A Study of the Components in Developing Human Resource Management Strategies of Vocational College Administrators Under the Office of Vocational Education Commission in Nongbualamphu Province - Inphusa, Siwakorn; Mahahing, Prachitr; Hapa, Yingsan (Journal of Graduate MCU KhonKaen Campus, 2025)
This The objective of this research was to identify the components of personnel management strategy development for administrators at vocational colleges under the Nong Bua Lam Phu Provincial Office of Vocational Education. The study employed a mixed-methods approach, combining document synthesis with component validation from nine experts in education and research. Data were collected using a validated 5-point rating scale questionnaire and analyzed using the mean and standard deviation, with an acceptance threshold set at a mean score of 3.51 or higher. The findings revealed two main components: 1) Strategy Development (15 indicators), comprising environmental assessment, direction setting, strategic issue identification, implementation, and evaluation; and 2) Personnel Management (23 indicators), consisting of manpower planning, recruitment and appointment, development, retention, and performance evaluation. Expert validation confirmed that all components were highly appropriate, with particular emphasis on personnel development and retention, reflecting the importance of continuous potential enhancement and morale building. The study concludes that the developed model is feasible for practical implementation within the vocational college context. It provides administrators with a strategic framework to design effective personnel management systems that align with national education policies and local contexts sustainably.